Microplastic pollution as a possible threat for an arctic reef system and its association of ecosystem engineers - Pyko, Ines Anna; Löder, Martin; Schulbert, Christian; Wisshak, Max; Laforsch, Christian; Munnecke, Axel; Teichert, Sebastian (54th European Marine Biology Symposium, 2019)
The coralline red alga Lithothamnion glaciale forms rigid frameworks of magnesium calcite. The shelfs around the high arctic Svalbard archipelago (northern Norway) are intensely covered by these so-called rhodoliths. Drilled by boring mussels of the species Hiatella arctica , many rhodoliths become hollow ecospheres, inhabited by a great variety of benthic taxa. Thereby, these rhodolith communities can be regardedas arctic reef structures and increase the local biodiversity significantly, comparable to corals in the tropics. They also provide a possible nursery ground for fish. We report the first findings of microplastic ingested by individuals of H. arctica. Altogether, we identified eight different types of polymers via F-spectroscopy within the rhodolith-colonizing bivalves. The potential consequences for the bivalves can be manifold, including a negative impact on their function as an ecosystem-engineering organism. This would also affect the complete ecosystem of the Svalbard Shelf and its biodiversity.
Keywords: Arctic; biodiversity; ecosystem engineers; microplastic